The Effect of Giving Rewards and Punishments on Employee Performance Through Job Satisfaction at PT. Umega Sembilan Berlian Airumeg AMDK Factory - Duri, Lara Vika; Ramdani Bayu Putra; Mutia Seplinda; Hasmaynelis Fitri (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
"The Effect of Giving Rewards and Punishments on Employee Performance Through Job Satisfaction at the Airumeg AMDK Factory PT. Umega Sembilan Berlian" Under the Guidance of Dr. Ramdani Bayu Putra, SE., MM and Mrs. Mutia Seplinda, S.Sc., M.Sc. This research aims to determine the effect of rewards and punishment on employee performance through job satisfaction at the Airumeg AMDK Factory PT. Umega Sembilan Berlian. Data collection methods through interviews, questionnaires, observation and documentation, with a sample of 80 respondents. The analysis method used is the Measurement Model Test (Outher Model) and structural model testing (Inner Model). It is obtained that: Rewards have a big impact on how satisfied you are at work. Punishment has a big impact on how happy someone is at work. Rewards have a big impact on how well employees perform. Punishment has a big impact on how well an employee performs. Employee performance is greatly influenced by job satisfaction